Organizational Behavior Impact on Work Productivity (Observed From Employee’s Individual Characteristics, Discipline, and Competence) - Subarto (International Journal of Integrative Sciences, 2023)
This study is about to discover the correlation between individual traits, discipline, and skill variables to organizational behavior which outcome is to determine job satisfaction variables of employee performance. This research method uses multiple linear regression and simple linear regression analysis, this study uses the basic population which is employees. The result shows individual parameters have a positive significance on organizational behavior. The result of individual characteristics on organizational behavior is 40.1 with an equation of regression Y = 1.408 + 0.881 X1. The discipline variable has a positive significance on organizational behavior. The contribution of discipline to organizational behavior is 32.5% with the equation of regression Y = 3.730 + 0.965 X2. Individual characteristics, discipline, and competency variables simultaneously influence organizational behavior. The magnitude of individual characteristics, discipline, and competence related to organizational behavior is 55.5 while the equation of multiple linear regression is Y = 0.723 + 0.349 X1 + 0.260 X2 + 0.528 X3. Organizational behavior variables have a positive significance on the productivity of employees. The impact of organizational behavior on employee work productivity is 45.9% with the regression equation Z = 12.690 + 0.494 Y